Molecular Neuropathology of Astrocytes and Oligodendrocytes in Alcohol Use Disorders - Miguel-Hidalgo, José J. (Frontiers in Molecular Neuroscience, 2018)
Postmortem studies reveal structural and molecular alterations of astrocytes and oligodendrocytes in both the gray and white matter of the prefrontal cortex (PFC) in human subjects with chronic alcohol abuse or dependence. These glial cellular changes appear to parallel and may largely explain structural and functional alterations detected using neuroimaging techniques in subjects with alcohol use disorders. Moreover, due to the crucial roles of astrocytes and oligodendrocytes in neurotransmission and signal conduction, these cells are very likely major players in the molecular mechanisms underpinning alcoholism-related connectivity disturbances between the PFC and relevant interconnecting brain regions. The glia-mediated etiology of alcohol-related brain damage is likely multifactorial since metabolic, hormonal, hepatic, and hemodynamic factors as well as direct actions of ethanol or its metabolites have the potential to disrupt distinct aspects of glial neurobiology. Studies in animal models of alcoholism and postmortem human brains have identified astrocyte markers altered in response to significant exposures to ethanol or during alcohol withdrawal, such as gap-junction proteins, glutamate transporters or enzymes related to glutamate and GABA metabolism. Changes in these proteins and their regulatory pathways would not only cause gray matter neuronal dysfunction, but also disturbances in the ability of white matter axons to convey impulses. In addition, alcoholism alters the expression of astrocyte and myelin proteins and of oligodendrocyte transcription factors important for the maintenance and plasticity of myelin sheaths in white and gray matter. These changes are concomitant with epigenetic DNA and histone modifications as well as alterations in regulatory microRNAs that likely cause profound disturbances of gene expression and protein translation. Knowledge is also available about interactions between astrocytes and oligodendrocytes not only at the Nodes of Ranvier but in astrocyte-oligodendrocyte contacts through gap junctions and other forms of cell-to-cell communication that are now understood to be critical for the maintenance and formation of myelin. Close interactions between astrocytes and oligodendrocytes also suggest that therapies for alcoholism based on a specific glial cell type pathology will require a better understanding of molecular interactions between different cell types as well as considering the possibility of using combined molecular approaches for more effective therapies.